7.8k views
1 vote
A) 4 x -3 x 2 =
b) -2 x 5 x -4 =
c) -3 x -1 x -6 =

User MnkDude
by
5.2k points

2 Answers

3 votes

Answer:

a.4 x -3 x 2 =

use the rules for multiplication

-(4×3×2)

-(12×2)

=2

----------------------------------

b. -2 x 5 x -4 =

note:

-2×5(-4)

multiplying an even number of negative terms makes the product positive.

-2×5= 10

10×-4

=40

----------------------------------

C. -3 x -1 x -6 =

note:

multiplying an odd number of negative terms makes the product negative.

-(3×1×6)

=-18

User Ben Ford
by
5.4k points
4 votes

Answer:

a) 4 x -3 x 2 = -24

b) -2 x 5 x -4 = 40

c) -3 x -1 x -6 = -18

User OPK
by
5.6k points